The Influence of Socio-Cultural Context on the Pragmatic Competence of EFL Secondary School Students in Comprehending Literary Text - Khalaf AL Azzawi, Mohammed Diab; Sultan, Amra Ibrahim (Journal of Tikrit University for Humanities, 2024)
This study is concerned with investigating the influence of socio-cultural context on strategic and pragmatic competence of EFL secondary school students. The aims of this study are: Finding out the influence of using socio-cultural context on strategic and pragmatic competence of EFL secondary school students’ achievement. finding out whether there is statistical significant difference between the mean score of experimental groups and that of the control group in the posttest in comprehending the To achieve these aims the following hypotheses are posed: There is no statistically significant difference between the mean score of experimental groups and control group by using literary context learning on strategic and pragmatic competence. There is statistical significant difference between the means score of the two experimental groups achievement who are taught by using socio-cultural context approach. Finally some recommendations and suggestions for further studies are put forward.